POLA DISTRIBUSI DIAMETER TANAMAN BALANGERAN (Shorea balangeran) DI LAHAN RAWA GAMBUT PROVINSI KALIMANTAN TENGAH: Cakra Birawa dan Wahyudi - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACK Balangeran is the commercial species and it grow well at the peat swam forest, initially. Conservation and cultivation of balangeran (Shorea balangeran Korth. Burck.) plant at the peat swamp land is the correct action with the reason this species is included the critically endangered species at the short future. This research was aimed to know the normality of balangeran growth that planted at the peat swamp land using the distribution of diameter approach. The research was conducted at the arboretum area of Plantation and Forestry Office, Pulang Pisau District, Central Kalimantan Province, Forestry Research Agency of Banjarbaru-KHDTK Tumbang Nusa and community balangeran plants. Plants of balangeran with age class namely 2, 3, 4, 5, 7, 8, 13, and 17 years old, with spacing of plants of 3 m x 6 m, were measured their diameter respectively, using census method, in order to collect the distribution of balangeran plants diameter. Research result showed that the diameter distribution of balangeran plants at the 2, 3, 4, 5, 7, 8, 13, and 17 years old are normaly with their graphics are similar with bell-parabolic, with polynomial models are D2= 6.818,2x4 – 11.131x3 + 5.700x2 – 943,3x + 50; D3= 5,8589x3 – 33,24x2 + 57,46x – 26,795; D4= 0,1377x4 – 2,9506x3 + 19,355x2 – 37,996x + 22,583; D5= 0,0012x6 – 0,0543x5 + 0,9671x4 – 8,2095x3 + 32,268x2 – 46,598x + 27,5; D7= 0,0743x4 – 1,4757x3 + 8,0073x2 – 6,4427x + 0,3333; D8= 0,158x3 – 3,4854x2 + 20,256x – 10,475; D13= = -0,0042x4 + 0,1642x3 – 2,1947x2 + 10,713x – 8,4965 dan D17= -0,7857x2 + 2,6143x + 7,6 respectively. Keywords: Balangeran, diameter, distribution, normaly, parabolic.